Liability of Online Platforms for Copyright Infringements in the Light of Judgments of the CJEU in the YouTube/Cyando and Poland Cases - Krajnc, Saša (Digital Platforms: Legal And Economic Challenges, 2024)
Article 17 of the Directive on Copyright in the Digital Single Market established a new liability regime for operators of large online platforms, imposing on them obligations of either obtaining a copyright license for copyrighted content shared by their users or preventing the availability of infringing content on the platform. The controversial provision sparked widespread public debate and resulted in two landmark decisions of the Court of Justice of the EU. One dealing with the legitimacy of Article 17 and the other with its applicability specifically to YouTube, and by extension similarly functioning platforms. While case Poland affirms the proportionality of Article 17, case YouTube/Cyando directly clashes with the provision, leaving in its wake an uncertain legal situation for online service providers, rightsholders and users alike.